EFEKTIVITAS METODE AL-MIFTAH LIL ULUM DALAM PEMBELAJARAN BAHASA ARAB INSTITUT AGAMA ISLAM AL-ZAYTUN INDONESIA TAHUN 2024 - Aqidah Tin Sholihah; Henri Peranginangin Tanjung; Iis Susiawati (STKIP Subang, 2025)
This study examines the effectiveness of a grammatical learning method in Arabic at the Al Zaytun Islamic Institute of Indonesia in 2024. The background of this research is the difficulty of learning Arabic caused by uninteresting learning methods, limited learning resources, and lack of student motivation to see the practical benefits. This study aims to evaluate the effectiveness of al miftah lil ulum method in Arabic language learning at Al-Zaytun Islamic Institute of Indonesia in 2024. This method has been widely used in Arabic language teaching in various Islamic educational institutions. However, its effectiveness still needs to be researched more deeply to provide empirical evidence on the extent to which the al-miftah lil ulum method can help students in mastering complex Arabic grammar. The research sample involved 64 PBA students who were selected by purposive sampling and divided into two groups. The experimental group received Arabic grammar learning using the al-miftah lil ulum method, while the control group used the conventional method. Data on learning outcomes were collected through pretest and posttest, then analyzed by paired t-test. The results showed a significant difference between pretest and posttest scores in the experimental group (0,000 < 0,05). This indicates the effectiveness of the al-miftah lil ulum method in improving students' Arabic grammar learning outcomes. This research has important implications for teachers, students, and Arabic curriculum development in higher education. The al-miftah lil ulum method can be an effective alternative in learning grammar. However, further research with a more robust experimental design and a larger sample is needed to strengthen these findings. Keywords: Al-miftah lil ulum, Arabic language learning, Arabic grammar, one-group pretest-posttest.